Effects of Density on Production of Hybrid Catfish in Intensively Aerated Earthen Ponds where Dissolved Oxygen is Not a Limiting Factor. (19th August 2019) - Torrans, Les; Ott, Brian
Abstract: Research has demonstrated that by maintaining the minimum dissolved oxygen (DO) concentration in earthen ponds at or above 3.0 ppm, feed intake and growth of Channel Catfish Ictalurus punctatus, Blue Catfish I. furcatus, and hybrid catfish (female Channel Catfish × male Blue Catfish) may be doubled relative to those achieved with the oxygen management regimes typically used on commercial catfish farms. In earlier studies using only emergency aeration or low levels of fixed aeration, the direct effect of stocking rate has been confounded by lower morning DO concentrations in ponds stocked at higher densities due to higher feed input and fish biomass. Although higher stocking rates in those studies did produce greater yields, individual fish growth and feed intake may have been impacted by lower DO levels while appearing to be a direct density effect. In this study, production of hybrid catfish, which were fed daily to satiation in earthen ponds with no water exchange, was compared at low (5, 000 fish/acre) and high (20, 000 fish/acre) stocking rates while using controlled intensive aeration to maintain a minimum DO over 3.0 ppm in all ponds through the study. We achieved an average net production of 27, 704 lb/acre at the higher stocking rate compared to 10, 176 lb/acre at the lower stocking rate. Although this is the highest yield reported thus far in traditional static‐water earthen ponds in the southern USA, it may not be the maximum production possible. The average weight of harvested fish was higher at the lower density (2.2 lb versus 1.6 lb), but the feed conversion ratio was identical (1.8) at the two densities. Our data indicate that when morning DO is maintained above limiting concentrations, other factors such as direct density interactions (aggression and/or inhibitory pheromonal feedback) and/or water quality variables unrelated to morning DO—specifically un‐ionized ammonia—may play a role in catfish feed intake and growth but not food conversion.